Usulan Perbaikan Kualitas Produk POY menggunakan Pendekatan Quality Control Circle dan Delphi di Departemen CP-3 PT. Indo-Rama - Rahmayanti, Nina; Iskandar, Hendi; Fata, Afif Fawa Idul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. Indo-Rama Synthetics Tbk is a textile manufacturing company that produces Partially Oriented Yarn (POY) in the CP-3 Department. During the January-March 2025 period, defective products amounted to 1,396 bobbins, or an average of 0.16% of the total monthly production. Although small in percentage, these defects impact increased rework activities, decreased efficiency, and potential delivery delays. This study aims to identify the root causes of the defects and develop improvement proposals using the Quality Control Circle method, as well as evaluate them through the Delphi approach. The analysis revealed two main defects: No Tail Yarn (35%) and Unstandardized Bobbins (35%). The causes include factors related to methods, machinery, and human factors. The proposed improvements include using permanent markers, routine inspections, tracking service life, protecting guides with visual safety markings, and re-socializing procedures and disciplinary action. The implementation of these improvements is estimated to reduce defects by up to 65%.